2011
DOI: 10.1177/0886260511416463
|View full text |Cite
|
Sign up to set email alerts
|

Gender Symmetry in the Self-Reporting of Intimate Partner Violence

Abstract: Research has not conclusively determined whether men and women are equally likely to commit intimate partner violence (IPV). One explanation for the disparity in previous findings may be gender-based differences in reporting styles. The present study investigated whether there was any gender difference in self-reported IPV prevalence. A total of 3,740 Chinese couples from a representative population in Hong Kong were interviewed. Self-reports of men-to-women and women-to-men IPV between spouses were compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 50 publications
(101 reference statements)
1
40
0
5
Order By: Relevance
“…We found that 32 studies used data collection instruments, of which 15 (46.87%) worked with the CTS or CTS2, or specific subscales of these instruments (Ackerman, 2012;Bates, Graham-Kevan, & Archer, 2014;Chan, 2012;Jaquier & Sullivan, 2014;Johnson et al, 2014;Leonard, Winters, Kearns-Bodkin, Homish, & Kubiak, 2014;Lövestad & Krantz, 2012;Marshall et al, 2011;Renner, Habib, Stromquist, & Peek-Asa, 2014;Sillito, 2012;Sullivan et al, 2010;Volpe et al, 2012;Zanoni, Warburton, Bussey, & McMaugh, 2014 In regard to the characteristics of participants / samples of the studies, 22 empirical studies used women and men. Of the studies that used women and men, only five conducted their research with couples (Chan, 2012;Leonard et al, 2014;Marshall et al, 2011;Renner et al, 2014;Tanha, Beck, Figueredo, & Raghavanet, 2010).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We found that 32 studies used data collection instruments, of which 15 (46.87%) worked with the CTS or CTS2, or specific subscales of these instruments (Ackerman, 2012;Bates, Graham-Kevan, & Archer, 2014;Chan, 2012;Jaquier & Sullivan, 2014;Johnson et al, 2014;Leonard, Winters, Kearns-Bodkin, Homish, & Kubiak, 2014;Lövestad & Krantz, 2012;Marshall et al, 2011;Renner, Habib, Stromquist, & Peek-Asa, 2014;Sillito, 2012;Sullivan et al, 2010;Volpe et al, 2012;Zanoni, Warburton, Bussey, & McMaugh, 2014 In regard to the characteristics of participants / samples of the studies, 22 empirical studies used women and men. Of the studies that used women and men, only five conducted their research with couples (Chan, 2012;Leonard et al, 2014;Marshall et al, 2011;Renner et al, 2014;Tanha, Beck, Figueredo, & Raghavanet, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…For some, the predominant was a theoretical research of controversies existent in the literature on gender a/symmetry (Chan, 2011;Enander, 2011;Hamby, 2015;LanghinrichsenRohling, 2010;Stark, 2010;Winstok, 2015). In other cases, the influence of male and female in different models of relationships was analyzed: in heterosexual individuals (Marshall, Jones, & Feinberg, 2011), homosexual couples (Messinger, 2011), married (Chan, 2012), separated (Johnson, Leone, & Xu, 2014) or dating (Hamby & Turner, 2013;Volpe, Hardie, & Cerulli, 2012). Another highlight for the goals was the interest in validating (Lehmann, Simmons, & Pillai, 2012) or exploring (Nybergh, Taft, & Krantz, 2012) instruments, as well as to answer the questions made on the validity of the Conflict Tactics Scale (CTS) or the Revised Conflict Tactics Scale (CTS2) (Straus, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have even found larger extent of violence perpetrated by females (see the metaanalysis elaborated by Archer, 2000). In this context, research should not only concentrate on prevalence and incidence rates of IPV, but it should also examine its severity, the consequences and the motivations, as well as situational aspects and the couple dynamics (e.g., Tjaden & Thoennes, 2000;Walklate, 2001;Dobash & Dobash, 2004;Johnson, 2006;Chan, 2012).…”
Section: Researching Violence Against Men: a Symmetry Questionmentioning
confidence: 99%